1997
DOI: 10.1046/j.1365-2613.1997.260359.x
|View full text |Cite
|
Sign up to set email alerts
|

Dietary vitamin E supplementation inhibits thrombin‐induced platelet aggregation, but not monocyte adhesiveness, in patients with hypercholesterolaemia

Abstract: Several recent studies have indicated the possible beneficial effects of antioxidants, specifically vitamin E, in primary and secondary coronary prevention. These studies suggest that a diet enriched in vitamin E is insufficient to have a significant protective effect, whereas supplements, in excess of 200 international units (IU) per day, are efficacious in preventing coronary disease in both men and women. The mechanisms by which vitamin E may exert its protection are uncertain, but, vitamin E is lipophilic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 36 publications
0
22
0
Order By: Relevance
“…Supplementation of hypercholesterolaemic patients with vitamin E (267 mg α-TE/d for 6 weeks) resulted in a significant inhibition of thrombin-induced aggregation (Williams et al 1997). After 6 weeks supplementation, the mean concentration producing 50 % maximum effect for thrombin-induced aggregation increased 132 % (P < 0·05).…”
Section: Platelet Functionmentioning
confidence: 96%
See 1 more Smart Citation
“…Supplementation of hypercholesterolaemic patients with vitamin E (267 mg α-TE/d for 6 weeks) resulted in a significant inhibition of thrombin-induced aggregation (Williams et al 1997). After 6 weeks supplementation, the mean concentration producing 50 % maximum effect for thrombin-induced aggregation increased 132 % (P < 0·05).…”
Section: Platelet Functionmentioning
confidence: 96%
“…However, some authors (Williams et al 1997) are of the opinion that the effects of vitamin E on platelet function could explain in part its anti-atherogenic properties.…”
Section: Platelet Functionmentioning
confidence: 99%
“…As shown in Table 4, among the 7 trials [122][123][124][125][126][127][128] in patients at risk of cardiovascular disease, 5 were performed in patients with diabetes mellitus. In these 5 trials, [122][123][124][125][126] the daily amount of vitamin E ranged from 100 to 600 IU, and follow-up lasted from 2 to 10 weeks.…”
Section: Vitaminsmentioning
confidence: 99%
“…125 In the remaining 2 studies performed in smokers or patients with dyslipidemia, inhibition of or no change in platelet function, respectively, was reported. 127,128 Globally considered, trials exploring the effect of vitamin E on platelet function inconsistently showed an inhibitory property in healthy subjects. The positive data obtained in diabetic patients are of some interest but are flawed by several methodological reasons, including nonsystematic analysis of oxidative stress and antioxidant status, open design, and small sample size.…”
Section: Vitaminsmentioning
confidence: 99%
“…These events are relevant to the onset of in ammation as well as in the early stages of atherogenesis. ®-Tocopherol inhibits aggregation of human platelets by a PKCdependent mechanism both in vitro and in vivo (53,(67)(68)(69). Also°-tocopherol decreases more potently than ®-tocopherol, suggesting that an antioxidant mechanism is not applicable given the lesser antioxidant activity of the latter relative to ®-tocopherol (68).…”
Section: Non-antioxidant Molecular Properties Of ®-Tocopherolmentioning
confidence: 99%